Crisis Communication Management in Law Enforcement Support Agencies (Study of the Financial Transaction Reports and Analysis Center) - Andriyanto, Tri; Hendriyani, Hendriyani (UI Scholars Hub, 2024)
This study aims to analyze and evaluate crisis communication management in institutions that support law enforcement, with a study at a national institution that supports law enforcement. The analysis is carried out by integrating theories and concepts from crisis communication management in the pre-crisis, during-crisis, and post-crisis stages and their relation to the image restoration strategy that is carried out when a crisis occurs when an institution discloses a case to the public. This study is qualitative research supported by issue monitoring data. Data were obtained through in-depth interviews with internal and external informants as the main data, and document studies in the form of media monitoring reports and related documents. The findings of this study indicate that crisis communication carried out by institutions that support the law enforcement process does not comply with the ideal process/stages of crisis communication management. The reorganization in 2022 has removed the name of public relations from the organizational chart and moved the position of public relations staff to another division, which has reduced the role and number of public relations personnel. Confidentiality of data and information causes barriers between units that make public relations have difficulty identifying the substance of the problem when potential crises begin to appear in the public. However, several crisis responses undertaken have played a role in resolving the crisis as well as restoring the image of the institution, such as in the use of the evade responsibility strategy which states that the actions taken are follow-ups from related institutions.